2015
DOI: 10.1016/j.cmi.2015.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Impact of obesity on the risk of wound infection following surgery: results from a nationwide prospective multicentre cohort study in England

Abstract: We sought to assess the impact of body mass index on the risk of surgical site infection in a prospective cohort study of 206 National Health Service (NHS) hospitals in England between 2007 and 2011. Body mass index was available for 159,720 of 350,089 operations among patients undergoing abdominal hysterectomy, coronary artery bypass graft, hip replacement, knee replacement, or large-bowel surgery. Among these patients, the risk of surgical site infection ranged from 0.65% for knee replacement to 11.04% for l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
82
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(92 citation statements)
references
References 25 publications
6
82
1
3
Order By: Relevance
“…This percentage is similar to that reported by different authors: 24 % De Groot et al [38], 24 % Koski et al [20], and 16 % De Boer et al [41]. Although some studies have shown a correlation between complication and obesity [35, 42, 43], diabetes, absence of drainage, and complicated fractures [21], in our series, only Sanders III fractures showed a higher risk (odds ratio (OR) = 4.51).…”
Section: Discussionsupporting
confidence: 89%
“…This percentage is similar to that reported by different authors: 24 % De Groot et al [38], 24 % Koski et al [20], and 16 % De Boer et al [41]. Although some studies have shown a correlation between complication and obesity [35, 42, 43], diabetes, absence of drainage, and complicated fractures [21], in our series, only Sanders III fractures showed a higher risk (odds ratio (OR) = 4.51).…”
Section: Discussionsupporting
confidence: 89%
“…For these patients, water-based aerobic activity may be a helpful suggestion. Total knee or hip arthroplasty may be an appropriate option, but extreme obesity is associated with significantly increased risk of surgical site infections [57]. With increasing scrutiny from hospitals and insurance companies on postoperative morbidity, orthopedists may be increasingly deterred from performing total knee arthroplasty in morbidly obese patients.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Second, ESRD-related platelet dysfunction may result in impaired hemostasis intraoperatively. 13 Third, DM is often severe within this population and requires meticulous medical management.…”
mentioning
confidence: 99%